Meromorphic close-to-convex functions satisfying a differential inequality - SHERGILL, Kuldeep Kaur; BILLING, Sukhwinder Singh (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
In the present paper, we study the differential inequality ... where f ∈ Σ and notice that the members of class Σ which satisfy the above inequality are meromorphic close-to-convex. Mathematics Subject Classification (2010): 30C45, 30C80.